Educational Research Planning: A Conceptual Literature-Based Study - Priatna, Tedi; Nurfauzi, Bayu Bambang; Fauziyyah, Isnina Fathi; Nurfauzan, Faiz; Widianti, Aliyah; Hasilah, Fauzah Nurul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Research planning is a crucial initial stage that determines the quality and direction of educational research. A well-structured research plan functions not only as a procedural guide but also as a form of academic accountability that ensures scientific coherence and rigor. This article aims to examine educational research planning from a conceptual perspective by emphasizing the integration of its main components. The method used in this study is a conceptual literature review of research methodology books and relevant scholarly articles in the field of educational research. The findings indicate that an effective educational research plan should include clear problem formulation, well-defined research objectives and significance, relevant theoretical and literature review, appropriate formulation of hypotheses or research questions, and accurate determination of population and sampling. The integration of these components is essential to maintain coherence, validity, and clear research direction. This article is expected to serve as a conceptual reference for students and educational researchers, particularly novice researchers, in developing systematic, logical, and scientifically grounded research plans.